2021
DOI: 10.4269/ajtmh.20-0657
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Time to Cryptosporidiosis in Bangladeshi Children is Associated with Greater Fecal IgA against Two Sporozoite-Expressed Antigens

Abstract: Cryptosporidiosis is common in early childhood, and both diarrheal and subclinical infections are associated with adverse developmental outcomes. Improved therapeutic medications may help reduce the burden of cryptosporidial diarrhea; however, an effective vaccine would be better able to prevent the detrimental impact of both diarrheal and subclinical disease. A more complete understanding of naturally occurring immunity may further inform strategies to develop an effective vaccine. In this prospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Children with high levels of fecal anti-Cp23 IgA were regarded as being previously exposed to the Cryptosporidium parasite even if the parasite had been missed during surveillance for sub-clinical infections. In previous work it was shown that even if Cryptosporidium DNA had not been identified high levels (> mean value) of fecal anti-Cp23 IgA at one year of age was associated with an increased resistance to cryptosporidiosis through age three [ 14 , 20 ]. In children with high fecal anti-Cp23 IgA there was an increase in the number of days until a child was reinfected and a subsequent decrease in the proportion of children in this group reinfected during years 2-3 (in children with high fecal anti-Cp23 IgA 77.8% were reinfected versus 92.2%)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with high levels of fecal anti-Cp23 IgA were regarded as being previously exposed to the Cryptosporidium parasite even if the parasite had been missed during surveillance for sub-clinical infections. In previous work it was shown that even if Cryptosporidium DNA had not been identified high levels (> mean value) of fecal anti-Cp23 IgA at one year of age was associated with an increased resistance to cryptosporidiosis through age three [ 14 , 20 ]. In children with high fecal anti-Cp23 IgA there was an increase in the number of days until a child was reinfected and a subsequent decrease in the proportion of children in this group reinfected during years 2-3 (in children with high fecal anti-Cp23 IgA 77.8% were reinfected versus 92.2%)…”
Section: Resultsmentioning
confidence: 99%
“…To this end, a community-based prospective cohort study of cryptosporidiosis was begun in 2014 [13]. The study subjects, born in an urban slum in Dhaka, Bangladesh were enrolled during the first week of life [13][14][15]. In humans and in animal models vaccination or prior infection resulted in partial protection against reinfection [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…(Slope: -0.294 ± 0.05; R squared value: 0.08; Significance p < 0.0001). C) Relationship of all-cause diarrhea with HAZ at 3 years of age (p = NS).Mucosal IgA against the sporozoite Cp23 protein was associated with protection from growth falteringIn previous work it was shown in this cohort that a high level (> mean value) of fecal anti-Cp23IgA at one year of age was associated with an increased resistance to cryptosporidiosis through age three[14,20]. Here we additionally discovered that children with high levels (upper 50 th percentile) of fecal anti-Cp23 IgA at one year of age were protected from growth faltering through year 3(Fig 6).…”
mentioning
confidence: 77%
“…To this end, a community-based prospective cohort study of cryptosporidiosis was begun in 2014 [13]. The study subjects were born in an urban slum in Dhaka, Bangladesh and enrolled during the first week of life [13][14][15]. In humans and in animal models vaccination or prior infection resulted in partial protection against reinfection [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of mucosal Cryptosporidium Cp23-specific IgA were reported to delay parasite reinfection in young children and to protect them from diarrhea-associated growth faltering. This partial immunity is believed to be associated with acquired mucosal IgA ( 31 , 32 ). Similarly, oral immunization with live C. parvum oocysts stimulated Cryptosporidium- specific IgA in feces and mice became more resistant to a secondary challenge even after treatment with IFN-γ-neutralizing MAb.…”
Section: Discussionmentioning
confidence: 99%